Specificity of Transfer in Basic and Applied Perceptual-Motor Tasks - Proctor, Robert; Dunston, Phillip; So, Joey; Lopez-Santamaria, Bessy; Yamaguchi, Motonori; Wang, Xiangyu (University of Illinois Press, 2013)
We conducted research on transfer of skills using basic stimulus–response compatibility tasks and applied tasks requiring control of a hydraulic excavator simulator. The basic tasks show rapid acquisition of practiced spatial mappings, for which transfer is specific to the procedures used in training. The applied tasks show transfer across alternative control configurations that maintain practiced spatial mappings, as well as from part to whole practice. Transfer from simulated to real equipment also seems to occur; however, studies involving cooperation of academia and industry are needed to provide more definitive evidence on this question.